Metabolic Power in Team Sports - Part 2: Aerobic and Anaerobic Energy Yields - Osgnach, Cristian; di Prampero, Pietro Enrico (International Journal of Sports Medicine, 2018)
A previous approach to estimate the time course of instantaneous metabolic power and O2 consumption in team sports has been updated to assess also energy expenditure against air resistance and to identify walking and running separately. Whole match energy expenditure turned out ≈14% smaller than previously obtained, the fraction against the air resistance amounting to ≈2% of the total. Estimated net O2 consumption and overall energy expenditure are fairly close to those measured by means of a portable metabolic cart; the average difference, after a 45 min exercise period of variable intensity and mode, amounting to ≈10%. Aerobic and anaerobic energy yields, metabolic power, energy expenditure and duration of High (HI) and Low (LI) intensity bouts can also be estimated. Indeed, data on 497 soccer players during the 2014/2015 Italian "Serie A" show that the number of HI efforts decreased from the first to the last 15-min periods of the match, without substantial changes in mean metabolic power (≈22 W·kg−1) and duration (≈6.5 s). On the contrary, mean metabolic power of the LI decreased (5.8 to 4.8 W·kg−1), mainly because of a longer duration thereof, thus underscoring the need for longer recovery periods between HI.
Keywords: acceleration/deceleration; energy cost; oxygen consumption; walking/running; energy balance; high intensity/low intensity